PENGARUH PELATIHAN KERJA TERHADAP KUALITAS PELAYANAN DIMEDIASI OLEH KOMITMEN ORGANISASI PADA HOTEL UBUD KOTA MALANG - Rini Safitri; Zuniar Afifa (LPPM STIE YAPAN, 2020)
This study aims to determine the effect of job training and organizational commitment to service quality with the object of research in the Hotel Ubud, Malang. This research uses quantitative methods with sampling techniques that are saturated samples. The data analysis technique used is multiple regression. The results of the research and analysis show that job training and organizational commitment affect the quality of service. And the results of this study are the same as those conducted by previous researchers. Thus, it can be seen that job training provided at the Ubud City Hotel in Malang has a positive effect on the quality of service for company employees.